Міфологічний образ колісниці у графіці населення степів Східної Європи доби бронзи - Сергєєва, М.С. (Археологія, 2001)
У статті аналізуються зображення колісниць та возів з позицій їхнього міфологічного змісту. В работе анализируются графические изображения колесного транспорта, относящиеся к периоду ранней бронзы и к срубному времени. За исключением единичного петроглифа из Каменной Могилы, все рисунки выполнены в плановом стиле, характерном для большей части Евразии, являющемся графическим выражением космической символики колесницы. Восточноевропейская степь относится к ареалу формирования этого стиля. Изображения колесных экипажей представлены разными типами повозок и колесницами. Ранние изображения представлены только повозками, в период поздней бронзы среди рисунков полностью доминируют колесницы, что может свидетельствовать о возрастающей роли колесницы в идеологии. Более высокий семиотический статус колесницы по сравнению с повозкой подтверждается данными ритуала и мифологий индоевропейского круга.
Основы колесничных мифов могли складываться на обширной территории от Ближнего Востока до евразийских степей. В их окончательном оформлении несомненна роль индоевропейцев. The paper analyzes the graphical images of wheeled transport related to the Early Bronze Age and to the time of frames. Except for a single petroglyph from the Kam’yana Mohyla, all the drawings are accomplished in the planned style, which is characteristic of most of Eurasia and is a graphical expression of the cosmic symbolics of a chariot. The area of formation of this style is concerned with the East European steppe. Images of wheel carriages are presented by various vehicles and chariots. Early images include only vehicles. But among drawings of the Late Bronze Age, chariots dominate completely, which testifies to the growing role of chariots in the ideology. A higher semiotic status of chariots as compared with vehicles is confirmed by the data on the ritual and mythology of the Indo-European sphere.
The basis of the myths concerning chariots can be formed on the vast territory from the Middle East to the Eurasian steppes. In their final formation, the role of the Indo-Europeans is unquestionable.